Determinants of Economic Growth in The Provinces of Sumatra Island - Safitri Ayu Lestari; Muhammad Rachmad R; Erni Achmad (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to analyze the determinants of economic growth in the provinces of Sumatra for the period 2020-2024, emphasizing the role of foreign direct investment (FDI), government spending, and human resource quality as measured by the Human Development Index (HDI), as well as formulating improvement strategies. Background Problems There is economic growth inequality among provinces in Sumatra, where the GRDP differs in each province even though this region is an important contributor to Indonesia's national economy. Research Methods: This study uses panel secondary data from 2020-2024 obtained from the World Bank, Ministry of Finance, Central Statistics Agency, and improvement strategies using the AHP model. Finding/Results: Government Expenditure (GE) and HDI have a significant positive effect on economic growth. Meanwhile, FDI has a probability value of 0.1481 > 0.05, meaning it does not significantly affect economic growth. Conclusion: The results of this study confirm that economic growth in Sumatra is more influenced by the effectiveness of government spending and the quality of human development than by the amount of foreign investment alone. Investment, fiscal, and human resource development policies are key to promoting more inclusive and sustainable economic growth in Sumatra.